Ankle muscle strength discriminates fallers from non-fallers - Cattagni, Thomas; Scaglioni, Gil; Laroche, Davy; Van Hoecke, Jacques; Gremeaux, Vincent; Martin, Alain (Frontiers in Aging Neuroscience, 2014)
It is well known that centre of pressure (CoP) displacement correlates negatively with the maximal isometric torque (MIT) of ankle muscles. This relationship has never been investigated in elderly fallers. The purpose of this study was thus to analyse the relationship between the MIT of ankle muscles and CoP displacement in upright stance in a sample aged between 18 and 90 years old that included elderly fallers. The aim was to identify a threshold of torque below which balance is compromised. The MIT of Plantar flexors (PF) and dorsal flexors (DF) and CoP were measured in 90 volunteers: 21 healthy young adults (age: 24.1 ± 5.0), 12 healthy middle-aged adults (age: 50.2 ± 4.5), 27 healthy elderly non-fallers (age: 75.5 ± 7.0) and 30 elderly fallers (age: 78.8 ± 6.7). The MIT of PF and DF were summed to obtain the overall maximal ankle muscle strength. Body weight and height were used to normalize MIT (nMIT) and CoP (nCoP), respectively. nCoP correlated negatively with nMIT. 90% of elderly fallers generated an nMIT < 3.1 N∙m∙kg-1, whereas 85% of non-fallers generated an nMIT > 3.1 N∙m∙kg-1. The relationship between nMIT and nCoP implies that ankle muscle weakness contributes to increased postural instability and the risk of falling. We observed that below the threshold of 3.1 N∙m∙kg-1, postural stability was dramatically diminished and balance was compromised. Our results suggest that measuring ankle torque could be used in routine clinical practice to identify potential fallers.